Isolated Gastric Myeloid Sarcoma: A Case Report and Review of the Literature - Pankit Vachhani; Prithviraj Bose (Case Reports in Hematology)
Myeloid sarcoma represents the proliferation of myeloblasts of acute myeloid leukemia (AML) at extramedullary sites. While extramedullary involvement in AML is uncommon in itself, isolated myeloid sarcomas, that is, myeloid sarcomas without any bone marrow involvement, are extremely rare and pose a diagnostic and therapeutic challenge. Here, we present the case of a middle-aged woman with isolated myeloid sarcoma in the stomach—an organ seldom involved by this disease. Additionally, the literature on the epidemiology, diagnosis, pathology, prognosis, and therapeutic options in myeloid sarcomas has been reviewed.